Promotion of Wellbeing for Children of Parents With Mental Illness: A Model Protocol for Research and Intervention - Reedtz, Charlotte; van Doesum, Karin; Signorini, Giulia; Lauritzen, Camilla; van Amelsvoort, Therese; van Santvoort, Floor; Young, Allan H.; Conus, Philippe; Musil, Richard; Schulze, Thomas; Berk, Michael; Stringaris, Argyris; et al. (Frontiers in Psychiatry, 2019)
Background: The main objective of this project is to create a research and intervention model to promote large-scale implementation and evaluations of generic very brief interventions for children of parents with mental disorders (COPMI). Feasible interventions for COPMI aged 0-18 years are highly needed, as this is a large high-risk group in society. Reducing behavioral problems and enhancing wellbeing for families with parents affected by any mental disorder is an important preventive initiative. One key prevention strategy is to reduce the risk and expression of psychopathology in children and to promote wellbeing. The present model protocol offers an intervention for children of parents with mental disorders internationally based on a model already implemented in the Netherlands and Norway. Methods: Participants will be parents receiving treatment in mental health services in participating countries and their minor children aged 8-16 years. Participants should be randomized into an intervention group or control group. Data should be retrieved from electronic patient journals (demographics, DSM 5/ ICD-10, SCID, MINI) as well as from assessment measures administered at baseline and follow-up, including the KIDSCREEN-27, Strengths and Difficulties Questionnaire (SDQ), Parents’ evaluations of developmental status (PEDS), Parenting Sense of Competence (PSOC), Resilience Scale for Adolescence (READ), Guilt and Shame Questionnaire for Adolescents of Parents with Mental Illness (GSQ-APMI), Mental Health Literacy Scale and Parent-Child Communication Scale. Results: The hypothesis is that there will be improvements of child behavioral and emotional problems, and outcomes in the project will be reported in terms of parent´s diagnosis, child behavioural and emotional problems, child wellbeing, family communication and functioning, as well as participants’ satisfaction. Discussion: This multi-site international protocol will focus the attention of European scientific and policy makers towards COPMI. This young segment of the population is presently almost completely neglected in most European health policies, despite having a large burden of disability and being at risk of transgenerational transmission of psychopathology. We will further discuss the feasibility of a very brief intervention aiming at preventing mental disorders in young people.